Using a Theory of Practice to Clarify Epistemological Challenges in Mixed Methods Research: An Example of Theorizing, Modeling, and Mapping Changing West African Seed Systems. (July 2017) - Jones, Kristal
This article argues that Bourdieu's theory of practice offers a unified epistemological foundation for mixed methods research by emphasizing the reflexive and iterative nature of knowing, and the relational aspects of knowledge construction. The increasing presence of spatial data and tools in research fields that focus on sociospatial phenomena suggests that visual representation can facilitate the resituating of objective patterns within a subjective context of geographic and symbolic space. The article presents the foundations of the theory of practice as a unifying framework for mixed methods research that incorporates spatiality. The article then offers an example of empirical research that characterizes changing seed systems in West Africa using the theory of practice to guide mixed methods research and analysis.